Urgensi Transformasi Pelayanan Publik melalui E-Government Pada New Normal dan Reformasi Regulasi Birokrasi - Anggita Doramia Lumbanraja (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
Covid-19 pandemic has a significant impact on society in Indonesia. New Normal discourse will be applied soon in Indonesia. Basically, it will give the same restriction and limitation of the interaction between individuals. Before pandemic, Conventional Public services required direct interaction between citizens and public servants in public office. But then, there will be a limitation to this direct interaction, and it also has to switch into the online services model. This study examined the urgency of the transformation of public services during the New Normal period through E-Government. This research used the normative juridical method. The author finds that the use of e-government in Indonesia is still far below Singapore. Indonesia needs to optimize the use of vertical and horizontal integration models that present one-stop service network services that require the transformation of public services from the Old Public Administration model to the New Public Service. This transformation should also be supported by regulatory reforms in the field of State Administration to increase synergy and harmonization between government institutions, so there is no overlapping of authority and conflicts between institutions that can hinder service delivery to the public. Keywords : Transformation of Government Services; E-Government; New Normal Abstrak Pandemi Covid-19 membawa dampak yang besar bagi masyarakat di Indonesia. Wacana New Normal yang akan diberlakukan, secara garis besar tetap membatasi interaksi antar individu. Pelayanan publik yang selama ini dilakukan dengan beinteraksi secara langsung harus dibatasi bahkan harus beralih kepada pelayanan secara online. Penelitian ini hendak mengkaji urgensi transformasi pelayanan publik pada masa New Normal melalui E-Government. Penelitian ini menggunakan metode yuridis normatif. Penulis menemukan bahwa penggunaan e-government di Indonesia masih jauh di bawah negara Singapura. Indonesia perlu mengoptimalkan penggunaan model integrasi vertikal dan integrasi horizontal yang menghadirkan network service layanan satu pintu yang membutuhkan transformasi pelayanan publik dari model Old Administration Public menuju New Public Service. Hal ini perlu juga ditunjang dengan adanya reformasi regulasi di bidang Administrasi Negara untuk meningkatkan sinergitas dan harmonisasi antar lembaga pemerintah, agar tidak terjadi tumpang tindih kewenangan dan konflik antar lembaga yang dapat menghambat pemberian layanan kepada masyarakat. Kata Kunci : Transformasi Pelayanan Publik; E-Government; New Normal